(untitled) (KULT_online, 2013)
As the number of Spanish learners has been increasing throughout the past years, the editors of the present anthology call for an intensified discussion in the research field of Spanish didactics. The introduction of both the Common European Framework of Reference for Languages (CEFR) and the learning standards for English and French in secondary schools prepared the way for competence-oriented teaching and learning arrangements in Spanish classes. The fact that numerous competencies are to be acquired – communicative and intercultural competence, method- and media-competence – may explain why we are dealing with a many-faceted field. It becomes even more complex if teaching approaches promoting plurilingualism or autonomous learning are taken into account. The contributions to this anthology offer an overview of the research area by presenting recent research projects with a practical orientation.